Three-dimensional soft material micropatterning via grayscale photolithography for improved hydrophobicity of Polydimethylsiloxane (PDMS) - Abdul Hamid, Intan Sue Liana; Beh, Khi Khim; Mohamed Omar, Mohammad Faiz; Mohamad Zain, Khairu Anuar; Abd Rhaffor, Nuha; Hamid, Sofiyah Sal; Abd Manaf, Asrulnizam (MDPI, 2022)
: In this present work, we aim to improve the hydrophobicity of a polydimethylsiloxane (PDMS) surface. Various heights of 3D PDMS micropillars were fabricated via grayscale photolithography, and improved wettability was investigated. Two approaches of PDMS replication were demonstrated, both using a single master mold to obtain the micropillar arrays. The different heights of fabricated PDMS micropillars were characterized by scanning electron microscopy (SEM) and a surface profiler. The surface hydrophobicity was characterized by measuring the water contact angles. The fabrication of PDMS micropillar arrays was shown to be effective in modifying the contact angles of pure water droplets with the highest 157.3-degree water contact angle achieved by implementing a single mask grayscale lithography technique.